Histone Deacetylases Inhibitors in Neurodegenerative Diseases, Neuroprotection and Neuronal Differentiation - Shukla, Surabhi; Tekwani, Babu L. (Frontiers in Pharmacology, 2020)
Histone deacetylases (HADC) are the enzymes that remove acetyl group from lysine residue of histones and non-histone proteins and regulate the process of transcription by binding to transcription factors and regulating fundamental cellular process such as cellular proliferation, differentiation and development. In neurodegenerative diseases, the histone acetylation homeostasis is greatly impaired, shifting towards a state of hypoacetylation. The histone hyperacetylation produced by direct inhibition of HDACs leads to neuroprotective actions. This review attempts to elaborate on role of small molecule inhibitors of HDACs on neuronal differentiation and throws light on the potential of HDAC inhibitors as therapeutic agents for treatment of neurodegenerative diseases. The role of HDACs in neuronal cellular and disease models and their modulation with HDAC inhibitors are also discussed. Significance of these HDAC inhibitors has been reviewed on the process of neuronal differentiation, neurite outgrowth and neuroprotection regarding their potential therapeutic application for treatment of neurodegenerative diseases.